A Foundation for Lorentz Force Based on Vibrating Strings as a Compact Fluid - Joshi, Narahari V. (Scientific research, 2014)
Several aspects related with Lorentz force are discussed in the light of the presence of vibrating strings. Strings are considered as a compact, tension and viscosity-free incompressible liquid. The motion of a charge particle, obviously, represents the “line of vortex” in the medium of fluid. The term (VXB) turns out to be the natural consequence of Vortex dynamics. The present investigation also reveals the nature of the magnetic field and explains why and how this additional term takes part in Lorentz force
Keywords: Lorentz Force; Origin for Magnetic Field; Fluid Dynamics; String Theory